Evolution of a gender tool: WEAI, WELI and livestock research - Colverson, Kathleen E.; Coble-Harris, L.; Galiè, Alessandra; Moore, E.V.; Muñoz, O.; McKune, S.L.; Singh, N.; Mo, R. (Elsevier, 2020)
The Women's Empowerment in Agriculture Index (WEAI) has been in use since 2012 and is widely recognized as one of the most rigorous tools to measure women's empowerment as a direct or indirect result of interventions from development projects. Changes to the WEAI have been ongoing and recent adaptations include measuring effects of interventions to improve livestock value chains on women's empowerment, as well as livestock related research. A multidisciplinary team of researchers at ILRI and Emory University developed the Women's Empowerment in Livestock Index (WELI), a new index to assess the empowerment of women in the livestock sector. While the WELI has been piloted in both Honduras and Tanzania, this article provides details on the latter case only. Currently, the Feed the Future Innovation Lab for Livestock Systems has employed the Abbreviated-Women's Empowerment in Agriculture Index (A-WEAI) to examine female decision-making in various projects from animal care knowledge and practices to feeding practices for children. Additionally, the development of the Project-Women Empowerment in Agriculture Index, currently in pilot testing, may allow for more insight into scaling existing projects. This article will discuss the adaptation and use of the WEAI for livestock research in Tanzania and Uganda, as well as future uses for contextually measuring women livestock producers' empowerment.